Uncovering Undergraduates’ Innovative Talents towards Employment Generation for National Growth and Development: Implications of Integrating Entrepreneurship Education into Science Teacher Education Programmes in Rivers State - Dr. Inibehe Sunday Etokeren; Dr. Chinda Worokwu (International Journal on Integrated Education, 2022)
Innovative talents remain imperative for maximum and proper utilization of a nation's limited resources to attain insurmountable advancement in scientific and technological achievements. Ideally, Innovation is a basic need for national progress and sustainable development mostly in developing nations like Nigeria. It is tough for any country to survive in today’s competitive and digital world without innovations and creativity. This study therefore, aims at examining the implications of integrating entrepreneurship education into science teacher education programmes towards employment generation for national growth and development. The sample consisted of 311 science education undergraduates from Rivers State Tertiary institutions, and the survey was conducted using a descriptive survey technique. The study was guided by three research questions and two hypotheses. Two Science Education and one Measurement and Evaluation Lecturers validated a 15-item questionnaire titled "Implications of Integrating Entrepreneurship Education into Science Teacher Education Program towards Employment Generation Questionnaire." The Pearson Product Moment Correlation coefficient was used to obtain the reliability coefficient of 0.79. To answer research questions, mean and standard deviation were employed, and the hypotheses was evaluated using the z-test at the 0.05 level of significance. The study's findings revealed that entrepreneurship education assists science education undergraduates in: possess practical entrepreneurial skills with positive attitude and business competencies, identify noble business opportunities, be creative and innovative, manage small-scale industries and take risk in business to ensure self-employment and self-reliance. This helps in reduction of unemployment and poverty rate and promote national development of Nigeria. In Rivers State, there was no significant gender difference in the influence of entrepreneurship education on the employment generation of science education undergraduates. Lecturers must therefore motivate scientific education students to develop entrepreneurial abilities, and science education graduates should be provided incentives to establish small businesses after graduation, among other recommendations.